Surgical procedures and techniques in robot-assisted retrograde para-aortic lymphadenectomy - Wang, Xinyou; Li, Ya; Zhu, Jinming; Wang, Jun; Han, Shichao; Na, Jing (Frontiers in Oncology, 2025)
BackgroundTo study the robotic-assisted abdominal aorta lymphadenectomy at the level of the left renal vein, aimed at standardizing and optimizing the surgical procedure.MethodsAll surgical procedures are guided by the theory of membrane anatomy, operating within the intermembrane spaces of embryonic compartments.ResultsUsing robotic assistance in a inverted position to perform lymphadenectomy of the abdominal aorta at the level of the left renal vein enables safe and reliable lymph node removal, combined with the concept of membrane anatomy, not only minimizes surgical bleeding but also helps reduce complications, such as vascular and intestinal injuries.ConclusionUtilizing robotics to perform lymphadenectomy of the abdominal aorta at the level of the left renal vein can achieve a more meticulous and refined surgical outcome. Precise surgical techniques contribute to standardizing and optimizing surgical procedures, thereby facilitating the learning process.